The Influence of Digital Technology on Learning Methods at SMA Negeri 5 Makassar City - A, Megawati; Sudika, Aryandi; Kamaruddin, Kamaruddin; Fatimah, Ana Cahayani (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
In the modern world of education, the integration of digital technology has become an important element in supporting the learning process in secondary schools. This study aims to analyze the influence of digital technology on learning methods and the effectiveness of student learning outcomes. This study uses a combination of qualitative and quantitative methods. Data were collected through in-depth interviews with teachers, observations of teaching and learning activities in the classroom, and distribution of questionnaires to students. The results of the study indicate that the use of digital technology has a significant impact on increasing student engagement in the learning process, the effectiveness of material delivery, and the development of their digital literacy skills. However, this study also found challenges in the implementation of digital technology, such as limited infrastructure, variations in teacher skills in utilizing technology, and unequal access among students. Therefore, ongoing support is needed to overcome these challenges so that the use of digital technology in education can be optimized to the maximum.